Effect of spatial constraints on the phase evolution of YFeO3-based nanopowders under heat treatment of glycine-nitrate combustion products. Issue 17 (1st December 2018) - Popkov, V.I.; Almjasheva, O.V.; Nevedomskiy, V.N.; Panchuk, V.V.; Semenov, V.G.; Gusarov, V.V.
Abstract: Formation and structural transformations of yttrium orthoferrite crystals have been studied using X-ray diffractometry, Mössbauer spectroscopy and transmission electron microscopy combined with electron microdiffraction. Said processes have been studied under heat treatment of glycine-nitrate combustion products. There have been identified formations of three structural yttrium orthoferrite modifications – amorphized hexagonal < h 1 > -YFeO3 ( P 63 cm ) and nanocrystalline hexagonal h 2 -YFeO3 ( P 63 /mmc ), as well as nanocrystalline orthorhombic o -YFeO3 ( Pbnm ), which are selectively formed depending on available three-dimensional confinements. Based on the analysis of changes in the fluid and size composition formulation, it has been proposed mechanism for formation and transformation of YFeO3 nanocrystals, including growth stage of h 2 -YFeO3 crystals due to amorphized phase of < h 1 > -YFeO3 up to critical size of about 15 nm and their subsequent transformation into orthorhombic form o -YFeO3 .